Axial Force Analysis and Roll Contour Configuration of Four-High CVC Mill - Guang-ming Liu (Mathematical Problems in Engineering, 2018)
In order to analyze the influence of technical parameters on work roll axial force of four-high continuous variable crown (CVC) mill, the deformation analyzing model with top roll system and strip was established based on influence function method. Then a CVC work roll curve designing scheme was proposed and it was carried out on some cold rolling mill considering the requirement of comprehensive work roll axial force minimization. The status of comprehensive work roll axial force is improved considering the rolling schedule that is beneficial to the roller bearing. Corresponding to the newly designed work roll contour, the backup roll end chamfer was designed considering comprehensive performance of interroll stress concentration, comprehensive work roll axial force, and strip shape control ability. The distribution of roll wear with newly designed backup roll contour is more even according to the field application data. The newly established roll configuration scheme is beneficial to four-high CVC mill.